Expansion of the available use classes in IEEE 802.15.4 networks for usage in the industrial environment - Odilson T. Valle (2012)
The usage of Wireless Sensor Networks (WSNs) in industrial environments has been steadily increasing, due to the reduced deployment and maintenance costs, when compared to the use of wired networks for connecting single I/O points in industrial applications. The most promising WSN standard is the one defined by the IEEE 802.15.4 standard. However, it does not support the adequate mechanisms to deal with the unreliable nature of an industrial communication environment. In this paper, we propose an extension of the use classes available for this standard, together with the proposal of adequate message retransmission schemes, in order to increase the reliability of message exchanges in industrial environments. To demonstrate the effectiveness of the proposed schemes, we present a simulation assessment of both the proposed message retransmission schemes and the Guaranteed Time Slots (GTS) mechanism, as defined by the standard. Â© 2012 IEEE.